Classification of edible salts using Raman spectroscopy coupled with principal component analysis - Entesar A Ganash; Daniah A Alsufyani; Reem M Altuwirqi (Materials Research Express)
Raman Spectroscopy is an effective optical technique for molecular vibration modes analysis. It has numerous advantages, such as being easy and rapid with no loss of accuracy, and can be applied to diverse samples. A Raman spectrum can be regarded as a fingerprint of the structure of molecules, which assists in characterizing materials. In this work, Raman Spectroscopy coupled with an exploratory tool such as principal components analysis (PCA) is applied to identify and categorize 24 edible salts available in the local market of Jeddah, Saudi Arabia. The results show the effectiveness of Raman spectroscopy and PCA analysis in discriminating the kinds of edible salts based on their origin (rock or sea). This was accomplished by analyzing a narrow region between 2800–3800 cm ^−1 (OH band), which was a sufficient region to obtain excellent discrimination between the salt samples based on their origin with an accuracy of 95.83%. However, the technique did not successfully detect the differences between natural and refined salts. This suggests the difficulty in distinguishing the chemically treated refined salts through Raman spectroscopy. This study could be used to classify edible salts based on their origin.